Capital Augmenting and Labor Augmenting Approach in Measuring Contribution of Human Capital and Education to Economic Growth - Milenko Popović (Montenegrin Journal of Economics, 2006)
In this paper an effort has been made to unveil some hidden and implicit assumptions that has been used in different models dealing with analysis and measurement of contribution of human capital to economic growth. We start from general production function with heterogeneous labor input and general production function with heterogeneous human and physical capital. By introducing different assumptions regarding partial elasticity of substitution between different factors of production we derived different models for human capital contribution. Apart from making hidden assumptions of existing models explicit, we also derived dozen of others models that can be used for same purposes. Among those newly proposed models especially important are those that are derived from general production function with heterogeneous human capital and that are based on assumption of unlimited partial elasticity of substitution between different kinds of human capital. First, they allow for more detailed sources of growth analysis. Second, they do not have any problem with wage premium increase experienced in last three decade, which make problematic usage of most of other models used so far.
Keywords: O41; C61; 330; economic growth; human capital; education; economic growth; human capital; education